1996
DOI: 10.1515/jpme.1996.24.3.221
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin dependent erythrocyte enzymes in newborns in relation to gestational age and birth weight

Abstract: In order to search for any difference in riboflavin and pyridoxine nutrition between term appropriate for gestational age (TAGA), term small for gestational age (TSGA) and preterm appropriate for gestational age (PTAGA) newborns, cord blood from 23, 19 and 20 infants, respectively, were studied, and red cell glutathione reductase (riboflavin-dependent) and glutamic oxaloacetic transaminase (pyridoxine-dependent) activities were measured, as well as their respective activity coefficients (GRase AC and GOT AC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Transport of vitamin B 6 to the fetus is most active during the last trimester, as assessed by an increase in the vitamin B 6 cord blood-to-maternal blood ratio (Schanler, 1988). However, Ramos et al (1996) found no difference in the cord RBC concentrations of aspartate aminotransferase, considered to be a biomarker for nutritional status of vitamin B 6 , among 23 AGA term infants, 19 SGA term infants, and 20 AGA preterm infants.…”
Section: Review Of the Literaturementioning
confidence: 71%
“…Transport of vitamin B 6 to the fetus is most active during the last trimester, as assessed by an increase in the vitamin B 6 cord blood-to-maternal blood ratio (Schanler, 1988). However, Ramos et al (1996) found no difference in the cord RBC concentrations of aspartate aminotransferase, considered to be a biomarker for nutritional status of vitamin B 6 , among 23 AGA term infants, 19 SGA term infants, and 20 AGA preterm infants.…”
Section: Review Of the Literaturementioning
confidence: 71%